Exclusive breastfeeding and professionals from the family health strategy - Marialda Moreira Christoffel; Ana Leticia Monteiro Gomes; Cássia Leoneuza Augusto Julio; Julia Florentino de Barros; Elisa da Conceição Rodrigues; Fernanda Garcia Bezerra Góes; Ana Maria Linares
ABSTRACT Objectives: to analyze the perception of health professionals about exclusive breastfeeding in Family Health Strategy units in the city of Macaé. Methods: qualitative study carried out in four units of the Family Health Strategy in the city of Macaé, Rio de Janeiro. Thirty health professionals were interviewed from March to May 2019. Textual contents were processed in the IRaMuTeQ® software by the Descending Hierarchical Classification. Results: professionals use different strategies for actions to promote, protect and support breastfeeding in prenatal consultations, but social and cultural determinants are important issues that interfere in this process, the involvement of the family being essential for the success of this practice. Final Considerations: health professionals, including nurses, need training and qualification to strengthen the support and social network of pregnant women and insert the family in the different strategies used to improve adherence to exclusive breastfeeding.